2016
DOI: 10.18632/oncotarget.8817
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SP1 by the mithramycin analog EC-8042 efficiently targets tumor initiating cells in sarcoma

Abstract: Tumor initiating cells (TICs), responsible for tumor initiation, and cancer stem cells (CSCs), responsible for tumor expansion and propagation, are often resistant to chemotherapeutic agents. To find therapeutic targets against sarcoma initiating and propagating cells we used models of myxoid liposarcoma (MLS) and undifferentiated pleomorphic sarcoma (UPS) developed from human mesenchymal stromal/stem cells (hMSCs), which constitute the most likely cell-of-origin for sarcoma. We found that SP1-mediated transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 50 publications
4
66
1
Order By: Relevance
“…In other types of tumors it has been described that trabectedin is able to induce apoptosis and G2/M cell cycle arrest and to reduce tumorsphere growth in CSC subpopulations derived from prostate cancer cell lines [43]. We also demonstrate that, unlike what we previously reported for doxorubicin [38], trabectedin represses the expression of multiple genes and pathways involved in the development and maintenance of the CSC phenotype. Despite the differential effects of trabectedin and doxorubicin on the expression of genes related to the CSC phenotype, trabectedin treatment of T-5H-FC#1-generated xenografts did not provide a therapeutic advantage over previously reported doxorubicin treatment of these xenografts [38] (Figure S3), thus reproducing the results observed in phase III clinical trials [44].…”
Section: Discussionsupporting
confidence: 61%
“…In other types of tumors it has been described that trabectedin is able to induce apoptosis and G2/M cell cycle arrest and to reduce tumorsphere growth in CSC subpopulations derived from prostate cancer cell lines [43]. We also demonstrate that, unlike what we previously reported for doxorubicin [38], trabectedin represses the expression of multiple genes and pathways involved in the development and maintenance of the CSC phenotype. Despite the differential effects of trabectedin and doxorubicin on the expression of genes related to the CSC phenotype, trabectedin treatment of T-5H-FC#1-generated xenografts did not provide a therapeutic advantage over previously reported doxorubicin treatment of these xenografts [38] (Figure S3), thus reproducing the results observed in phase III clinical trials [44].…”
Section: Discussionsupporting
confidence: 61%
“…Mithramycin is an antibiotic isolated from Streptomyces plicatus that binds to specific DNA regions to repress transcription of specific genes. Importantly, this compound was found to downregulate the expression of stemness-related genes (including SOX2 and ZEB1) in sarcoma cells (Tornin et al, 2016), and was also shown to have high efficacy for growth inhibition of a SOX2-positive cell population that propagates medulloblastoma (Vanner et al, 2014). Interestingly, mithramycin has been shown to be therapeutically effective in GBM patients in clinical studies conducted in the 1960s (Ransohoff et al, 1965), however further clinical use of this small molecule was hampered because of an unfavorable toxicity profile.…”
Section: Resultsmentioning
confidence: 99%
“…S1C), although its cytotoxic effect on CSC subpopulations was lower than that previously observed in nonselected adherent cultures (Figs. a and 1 b ) and also much lower than the effect of the mythramicin analog EC‐8042, a drug with reported activity on sarcoma CSCs …”
Section: Resultsmentioning
confidence: 93%
“…The viability of all cell lines in the presence and absence of drugs was determined using the Cell Proliferation reagent WST-1 (Roche, Mannheim, Germany) as described before. 37 The concentration of half-maximal inhibition of viability (IC 50 ) for each treatment was determined by nonlinear regression using the graphPad Prism software (La Jolla, CA). The existence of synergy in drug combinations was determined by calculating the combination index (CI) as described in Supporting information.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
See 1 more Smart Citation